Metabolic rates of ATP transfer through creatine kinase (CK Flux) predict clinical heart failure events and death - Bottomley, Paul A; Panjrath, Gurusher S; Lai, Shenghan; Hirsch, Glenn A; Wu, Katherine; Najjar, Samer S; Steinberg, Angela; Gerstenblith, Gary; Weiss, Robert G (Science translational medicine, 2013)
Morbidity and mortality from heart failure (HF) are high, and current risk stratification approaches for predicting HF progression are imperfect. Adenosine triphosphate (ATP) is required for normal cardiac contraction, and abnormalities in creatine kinase (CK) energy metabolism, the primary myocardial energy reserve reaction, have been observed in experimental and clinical HF. However, the prognostic value of abnormalities in ATP production rates through CK in human HF has not been investigated. Fifty-eight HF patients with nonischemic cardiomyopathy underwent ³¹P magnetic resonance spectroscopy (MRS) to quantify cardiac high-energy phosphates and the rate of ATP synthesis through CK (CK flux) and were prospectively followed for a median of 4.7 years. Multiple-event analysis (MEA) was performed for HF-related events including all-cause and cardiac death, HF hospitalization, cardiac transplantation, and ventricular-assist device placement. Among baseline demographic, clinical, and metabolic parameters, MEA identified four independent predictors of HF events: New York Heart Association (NYHA) class, left ventricular ejection fraction (LVEF), African-American race, and CK flux. Reduced myocardial CK flux was a significant predictor of HF outcomes, even after correction for NYHA class, LVEF, and race. For each increase in CK flux of 1 μmol g⁻¹ s⁻¹, risk of HF-related composite outcomes decreased by 32 to 39%. These findings suggest that reduced CK flux may be a potential HF treatment target. Newer imaging strategies, including noninvasive ³¹P MRS that detect altered ATP kinetics, could thus complement risk stratification in HF and add value in conditions involving other tissues with high energy demands, including skeletal muscle and brain.